Effect of different rehydration protocols and their immersion times on the fracture resistance of fragment reattachment in uncomplicated crown fractures: An in vitro study (Journal of Pharmaceutical Negative Results, 2022)
This study aims to evaluate the effects of different rehydration media and their immersion times on fracture resistance of fragment reattachment in uncomplicated crown fractures. 110 extracted sound human maxillary and mandibular incisors were randomly divided into 11 groups (n=10). The teeth were fractured 3mm away from and parallel to the incisal edge using diamond disc. Afterwards, the apical segments were stored in artificial saliva (Saleva), while the coronal segments underwent the dehydration-rehydration stages and grouped randomly into 5 (n=10, 10, 30, 30, 30). Group 1: control group (intact teeth); Group 2: 24 hours dehydration, no rehydration; Group 3: skimmed milk rehydration; Group 4: saline(0.45%) rehydration; Group 5: dextrose solution(50%) rehydration. Group 3,4,5 further sub-divided into A: 15 min, B: 30 min, C: 24 hours. Re-attachment was done with flowable composite resin. Fracture resistance tested with universal testing machine. Statistical analysis (p=0.05) done by One-way ANOVA, Two-way ANOVA and post-hoc Tukey’s test HSD. Fracture resistance: Group 1 (highest), Group 5 (higher), Group 2(least). Within study limitations, it is conclusive that preservation of tooth fragment in dextrose solution(50%) results in higher fracture resistance, followed by saline(0.45%) and skimmed milk, respectively.